Autocovariance and Linear Transformations of Markov Switching VARMA Processes - Cavicchioli, Maddalena (Central European Journal of Economic Modelling and Econometrics, 2014)
We study the autocovariance structure of a general Markov switching second-order stationary VARMA model. Then we give stable finite order VARMA(p∗, q∗) representations for those M-state Markov switching VARMA(p, q) processes where the observables are uncorrelated with the regime variables. This allows us to obtain sharper bounds for p ∗and q∗ with respect to the ones existing in literature. Our results provide new insights into stochastic properties and facilitate statistical inference about the orders of MS-VARMA models and the underlying number of hidden states.